Chill Accumulation Monitoring and Forecasting - Clyde W. Fraisse; Alicia Whidden (EDIS)
AE452, a 6-page illustrated fact sheet by Clyde W. Fraisse and Alicia Whidden, introduces a new web-based tool for agricultural producers to track and forecast chill accumulation during the winter season to reduce risks associated with climate variability in the southeastern U.S.A. Includes references. Published by the UF Department of Agricultural and Biological Engineering, January 2010.